Exploring the spatial epidemiology and population genetics of malaria-protective haemoglobinopathies - Hockham, C (2017)
Haemoglobinopathies, which include sickle-cell anaemia (SCA) and α- and β-thalassaemia, represent some of our few unequivocal examples of human evolution. The underlying genetic mutations reflect a recurring adaptation against one of the biggest infectious disease killers of humans, Plasmodium falciparum malaria. Inheritance of one copy of a sickle-cell or thalassaemic allele leads to protection against death from malaria, while two copies can result in a severe blood disorder. As a result, haemoglobinopathies have risen in frequency through balancing selection and pose a significant public health problem in parts of the world with a history of malaria transmission. Their study therefore lies at the interface between evolutionary biology and public health. In this thesis, I explore different aspects of the epidemiology and population genetics of haemoglobinopathies around the world. Using pre-existing epidemiological data, statistical and geostatistical methods and Geographic Information System tools, I develop detailed evidence-based maps of the α-thalassaemia allele frequency distribution and genetic diversity in Southeast Asia and sickle-cell allele frequency in India. Pairing these with birth data, I generate sub-national estimates of the number of newborns born with severe forms of α-thalassaemia and SCA in Thailand and India, respectively, together with uncertainty estimates. In addition, I use a flexible population genetic simulation model to explore evolutionary explanations for the contrasting spatial haplotype patterns observed for SCA and the severe form of β-thalassaemia (β0-thalassaemia) in sub-Saharan Africa and the Middle East, and resurrect a 20-year old question surrounding the genetic origin of sickle-cell. Understanding the fine-scale geographical heterogeneities in the distributions of malaria-protective haemoglobinopathies is critical for addressing basic science questions and applied public health queries. Working at the interface between evolutionary biology and public health has provided me with the opportunity to build a more complete overview of the neglected increasing public health burden that this group of human disorders represents.